Application of nano base lubricants in machining process for performance improvements / Mohd Sayuti Ab Karim - Mohd Sayuti , Ab Karim (2013)
For the various manufacturing industries, particularly aerospace and automotive applications, producing high-quality metal-based products is very important. During the turning and milling operations of metal workpieces, product quality is among the criteria with the potential to be improved by using a suitable lubrication system. The capability of the CNC milling process to produce complex shapes provides noteworthy advantages owing to its wide variety of parameter setups. In practice, the effectiveness of lubrication systems should be increased to enhance product quality. However, it is feasible to improve machining quality by introducing nanoparticles to the base lubricant, which becomes a nano-based lubricant. Nanoparticles within the lubricant reduce the friction at the toolworkpiece interface by means of rolling and sliding actions. In this research, nano-based lubricants containing SiO2, MoS2 and carbon onion nanoparticles were developed by mixing each of these types of particles with ordinary mineral oil. By using the L16(4)4 orthogonal array experimental design for machining parameter optimization in the hard turning process, improvements of 10.48%, 10.48%, 8.52%, 8.22% and 10.55% for cutting force, power consumption, surface roughness, chip thickness and cutting temperature were gained, respectively, as opposed to the smallest values obtained in the preliminary experiments. Subsequently, upon implementing the L16(4)3 orthogonal array experimental design to the hard turning process with SiO2 nano-based lubricant, power consumption was reduced by 37.19% compared with an ordinary lubrication system. From the Fuzzy logic approach, surface roughness and tool wear were found to be reduced by 23% and 15% when SiO2 nano-based lubricant was employed in the hard turning process rather than an ordinary lubrication system. On the other hand, implementing the L16(4)3 orthogonal array design of experiment with SiO2 nano base lubricant for the milling process reduced cutting force, surface roughness and cutting temperature by 25.02%, 26.28% and 29.34% respectively, compared with ordinary lubrication. Alternatively, to investigate the effect of different types of nano-based lubricant in milling, the L16(4)3 orthogonal array experimental design was utilized with a MoS2 nano-based lubricant. The outcome represents 2.62%, 2.56% and 0.04% enhanced cutting force, surface roughness and cutting temperature respectively, in contrast to the lowest values obtained from the initial experiments. Furthermore, performance enhancement in the milling process was additionally investigated by applying carbon onion nano-based lubricant in light of its tribological properties. The results signify that cutting force and surface roughness were reduced by 21.99% and 46.32% respectively, in the presence of optimum carbon onion in the lubrication system as opposed to using an ordinary lubrication system.